Political Dynasties and Local Spending in Indonesia - Dwi Putri Larasati; Jahen Fachrul Rezki (Department of Development Economics, Universitas Sriwijaya, 2023)
Does political dynasty affect local spending in Indonesia? Only a few articles have taken up the political economy issues in Indonesia This study provides empirical analysis that focuses on explaining the effect of the political competition through dynasty winning in the mayoral election to the local spending that focuses on functional-classified expenditure at the district level. Using the Regression Discontinuity Design (RDD) estimation, this study examines whether the dynasty mayor has different trends in the way to spend local expenditure compared to the non-dynasty mayors. Due to the limited political competition, this study finds the magnitude effect of the dynasty mayor on local spending that used to drive the regional economy. Compared to the non-dynasty mayors on a separate sub-dataset, this study finds different effects of a dynasty between the incumbent and the non-incumbent dynasty mayor on local spending. The incumbent dynasty mayor negatively affects ‘visible’ expenditure’ e.g., grant and social assistance expenditure, social protection expenditure, housing and public amenities expenditure, education expenditure, dan current expenditure. This study also finds negative effects of the political dynasty on local spending from the dynasty mayor elected during the period of simultaneous mayoral election (2015-2018).